1963
DOI: 10.1111/j.1478-4408.1963.tb02513.x
|View full text |Cite
|
Sign up to set email alerts
|

The Saturation Values, Rates of Dyeing, Rates of Diffusion, and Migration of Disperse Dyes on Heat‐set Polyester Fibres*

Abstract: Studies have been made of the dependence of saturation limits, rates of diffusion, rates of dyeing, and migration properties of a number of disperse dyes on polyester fibres upon the temperature at which the fibres have been heat‐set. Use of pure, crystalline dyes was found to give erratic results and therefore ultra‐dispersed commercial dyes were used in the investigation. The saturation limit and the average diffusion coefficient showed a minimum at a particular heat‐setting temperature. Values were calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 7 publications
3
27
0
Order By: Relevance
“…To get a clear impression for the dyeing conditions, the dyeing pressures are also given in the tables. The saturation coloration of Disperse Orange 13 in scCO 2 at 378K (105°C) and 550 kg/m 3 is 2.1 mass percent, close to the value reported in literature for aqueous dyeing at 100°C (2.0 mass percent) [17].…”
Section: Distribution Coefficientsupporting
confidence: 86%
“…To get a clear impression for the dyeing conditions, the dyeing pressures are also given in the tables. The saturation coloration of Disperse Orange 13 in scCO 2 at 378K (105°C) and 550 kg/m 3 is 2.1 mass percent, close to the value reported in literature for aqueous dyeing at 100°C (2.0 mass percent) [17].…”
Section: Distribution Coefficientsupporting
confidence: 86%
“…they were a measure of the rate of uptake. Merian et al (4), however, demonstrated that similar effects could be found when the equilibrium absorption values were considered. These authors also confirmed that other indications of the rate of dyeing, e.g.…”
Section: Introductionmentioning
confidence: 72%
“…Dyes on applying to acrylic dyeing showed similar observations as that on nylon (Table 3c). spectra of 4a, 4b, 4c and 5a, 5b, 5c dyes in THF-H 2 O mixtures with different water fractions (5 μM) On the other hand, dyes bond strongly to PET and are slightly affected by UV radiations [67,68]. Hence, PET is more suitable than nylon for the dyes under investigations.…”
Section: Color Co-ordinatesmentioning
confidence: 99%